Cooperation between Governmental and Non Governmental Organizations On Thailand-Myanmar Border Health Development - Kangvallert, Rossukon; Lawnub, Krisnan; Manimnakorn, Supawan; Ingkapakorn, Lampoon; Thammachart, Supparaporn (Journal of Health Science of Thailand, 2019)
This qualitative research was a situation analysis on public health issues and coordination between Governmental Organizations (GOs) and Non- Government Organizations (NGOs) along Thailand-Myanmar Border. Both qualitative and evidence-based quantitative data were collected in 10 provinces by focus group interviewing, in-depth interviewing, observation and document reviews. All data were analyzed and verified to ensure that the accuracy and consistency results were reported. Results of this study revealed that major public health problems along border area were communicable diseases, mother and child health including family planning, environmental health and narcotic in hill tribe areas. Eight of ten provinces have established coordinating mechanism working with local NGOs and international NGOs organizations. The key success factors included awareness of governmental authorities, regular meetings to share experiences and information between GOs and NGOs lead to more efficient cooperation and relationship. The weakness factors were no clear policy on Thailand- Myanmar border health development and different on language. Recommendations include setting up a collaborative frameworks which are site specific and health manpower development related to necessary skills, proactive working technique and communication skills. In addition, MOPH should establish a core coordinating body that could serve as a focal point in coordination of the Thailand-Myanmar border public health program implementation among related organizations at all levels.